The Shifting Profile of Africa in Twenty-First Century Black Canadian Writing - Cuder-Domínguez, Pilar (International Journal of English Studies, 2023)
The affective link with Africa was visible in those Black Canadian works composed in the late 1980s and early 1990s. In contrast, the profile of Africa has shifted for younger generations of Black diasporan writers in Canada. The purpose of this article is to open up a conversation into how Black Canadian affects, both concerning national identity and homeland connection, seem to have shifted roughly after 2000. In order to do so I analyse The Adventures of the Black Girl in Her Search for God (2017), a reinterpretation by Black Canadian playwright Lisa Codrington of George Bernard Shaw's 1932 short story of the same title. Her play was a milestone in the history of Black Canadian writing, because for the first time a Black Canadian playwright (and a woman, too) was invited to participate in one of Canada's most prestigious and longest-established theatre festivals, the Shaw Festival.